2000
DOI: 10.1093/hmg/9.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase at active centromeres and neocentromeres at metaphase

Abstract: A double-stranded 9 bp GTGAAAAAG pJ alpha sequence found in human centromeric alpha-satellite DNA and a 28 bp ATGTATATATGTGTATATAGACATAAAT tandemly repeated AT28 sequence found within a cloned neo- centromere DNA have each allowed the affinity purification of a nuclear protein that we have identified as poly(ADP-ribose) polymerase (PARP). Use of other related or unrelated oligonucleotide sequences as affinity substrates has indicated either significantly reduced or no detectable PARP purification, suggesting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…For example, both PARP-1 and PARP-2 localize to mitotic centromeres, the chromosomal regions where kinetochores form to capture microtubules from the mitotic spindle (Earle et al 2000;Saxena et al 2002a,b). In addition, several PARP enzymes, including PARP-1, PARP-3, and tankyrases, are associated with centrosomes, the cellular microtubule organizing center that functions as the spindle pole during mitosis (Smith and de Lange 1999;Kaminker et al 2001;Augustin et al 2003;Kanai et al 2003).…”
Section: Mitotic Apparatus Functionmentioning
confidence: 99%
“…For example, both PARP-1 and PARP-2 localize to mitotic centromeres, the chromosomal regions where kinetochores form to capture microtubules from the mitotic spindle (Earle et al 2000;Saxena et al 2002a,b). In addition, several PARP enzymes, including PARP-1, PARP-3, and tankyrases, are associated with centrosomes, the cellular microtubule organizing center that functions as the spindle pole during mitosis (Smith and de Lange 1999;Kaminker et al 2001;Augustin et al 2003;Kanai et al 2003).…”
Section: Mitotic Apparatus Functionmentioning
confidence: 99%
“…Remarkably, a number of recently identified partners of PARP-1 and PARP-2 such as CENP-A, CENP-B, Bub 3 (41)(42)(43) and Aurora B (L. Monaco, R. Loury, J. Mé nissier-de Murcia, M.…”
Section: Parps and The Mitotic Apparatusmentioning
confidence: 99%
“…In this report, we focused on PARP1 because it is reported to be a multifunctional protein and was recently found to act as a component of the centromere and the centrosome (21,30,47), which suggests that it may be a key factor for chromatin structure (51), replicated genome segregation, and partitioning (50), although it is best known as a target substrate for the caspases in apoptosis (53). In KSHV, a recent report showed that PARP1 interacts with RTA, an immediate-early protein that is a key factor for the induction of lytic replication (25).…”
Section: Vol 78 2004 Parp1 Binds With Kshv Tr and Modulates Its Repmentioning
confidence: 99%